The boy most likely to - Fitzpatrick, Huntley (Dial Books, 2015)
"When Tim and Alice begin to fall in love, Tim thinks he is finally on the right track, until the unexpected consequences of his drug-addicted and alcoholic past throw a wrench in his new life"--